2013
DOI: 10.1200/jco.2012.44.7888
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamic Effects and Mechanisms of Resistance to Vemurafenib in Patients With Metastatic Melanoma

Abstract: PURPOSE To assess pharmacodynamic effects and intrinsic and acquired resistance mechanisms of the BRAF inhibitor vemurafenib in BRAF(V600)-mutant melanoma, leading to an understanding of the mechanism of action of vemurafenib and ultimately to optimization of metastatic melanoma therapy. METHODS In the phase II clinical study NP22657 (BRIM-2), patients received oral doses of vemurafenib (960 mg twice per day). Serial biopsies were collected to study changes in mitogen-activated protein kinase (MAPK) signaling,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
275
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 334 publications
(286 citation statements)
references
References 30 publications
11
275
0
Order By: Relevance
“…Furthermore, NRASQ61R does not recapitulate all NRAS-driven mechanisms of resistance to BRAF inhibitors, as NRASQ61K have also been reported to be associated with an acquired resistant phenotype. 27 The focus of the current study was not on evaluating the frequency of NRASQ61R mutations in primary cutaneous melanoma, but on ascertaining the utility of a mutation-specific antibody. Therefore, our cases were not selected specifically to verify mutation rates.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, NRASQ61R does not recapitulate all NRAS-driven mechanisms of resistance to BRAF inhibitors, as NRASQ61K have also been reported to be associated with an acquired resistant phenotype. 27 The focus of the current study was not on evaluating the frequency of NRASQ61R mutations in primary cutaneous melanoma, but on ascertaining the utility of a mutation-specific antibody. Therefore, our cases were not selected specifically to verify mutation rates.…”
Section: Discussionmentioning
confidence: 99%
“…MEK1/2 mutations, including MEK1 Q56P , have been implicated in both single-agent BRAF and combination BRAF/MEK targeting therapy-acquired resistance in patients (18,21,(34)(35)(36). Single-agent assays demonstrated that relative to the parental BRAF V600E ::MEK1 wt cells, the double-mutant BRAF V600E ::MEK1 Q56P cells displayed a markedly reduced sensitivity to the BRAF inhibitors vemurafenib and dabrafenib and the MEK inhibitor trametinib (Fig.…”
Section: Bvd-523 Exhibits Activity In In Vitro Models Of Braf and Mekmentioning
confidence: 99%
“…RAS has been consistently described as a mechanism of resistance to BRAF inhibitors. It is well known that there is a switch in RAF isoform usage depending on whether BRAF or RAS is mutated (Table 3) [95][96][97][98][99][100][101]. In melanocytes in Table 3 Resistance to BRAF inhibitors.…”
Section: Nras As a Mechanism Of Resistance To Braf Inhibitors In Melamentioning
confidence: 99%